2021
DOI: 10.18844/wjet.v13i4.6269
|View full text |Cite
|
Sign up to set email alerts
|

Formation of information and professional competence of primary school teachers with Online Education.

Abstract: The aim of this research is to provide the formation of knowledge and professional competence of primary school teachers with online education. The research was conducted in the summer term of 2020-2021. 436 primary school teachers who continue their studies in Kazakhstan participated in the research. For the research, 6 weeks of online training on professional competence was given to primary school teachers. The measurement tool called "Online Education and Vocational Competence", which was developed by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Distance education, with its most general and simple definition, is the formal education process where students and teachers are not physically in the same place (Uaidullakyzy, 2021). In the distance education process, students and teachers physically connect by making use of teaching resources and interactive communication technologies in different environments (Bhuyan, 2021;Selvaraj et al, 2021).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Distance education, with its most general and simple definition, is the formal education process where students and teachers are not physically in the same place (Uaidullakyzy, 2021). In the distance education process, students and teachers physically connect by making use of teaching resources and interactive communication technologies in different environments (Bhuyan, 2021;Selvaraj et al, 2021).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…It is seen that the need for continuous education and developing technology has revealed the concept of university-taught distance education; it is defined as an educational institution where basic activities, such as distance education and research that should be found in a university, are carried out on the Internet to a large extent [13]. With this interpretation, it is thought that a well-designed distance education project can help develop the competencies required by the information society, provide a standardised education that will spread to all educational institutions, create employment, increase the quality and success of distance education, create standard and high-quality education materials and enable international competition [12].…”
Section: Introductionmentioning
confidence: 99%